Observations on dynamics of foraging hole construction of two leaf-feeding, soil-inhabiting Syntermes species (insecta: Isoptera) in an Amazonian Rainforest, Brazil - MARTIUS,Christopher (1998)
The intensity of construction of foraging access holes by two leaf-litter feeding, soil- inhabiting termite species, Syntermes molestus and Syntermes spinosus, in a Central Amazonian rain forest, was observed on consecutive nights for two weeks. Between 11 and 48 nest entrances per m2 were counted. Interaction between the two species was intense; some entrance holes were overtaken by the larger species during the observations; however, both species coexist in the area. A calculated minimum of 35 entrances/m2 is built every year by both species, emphasizing the importance of soil-burrowing termites for soil structure, aeration and water regime.